PELATIHAN APPRECIATIVE INQUIRY UNTUK MENINGKATKAN EFIKASI DIRI WIRANIAGA DALAM MELAKUKAN TUGAS PENJUALAN - , Nenylala BR Sitepu ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of this research is to know the influence of appreciative inquiry training in self efficacy for salesperson at their selling project. Self efficacy is very important for the salesperson for the inner power to complete the task because it makes they believe to them self be able to complete that task. Research subject consist of 36 salesperson, which separate by 18 at experiment group who get the appreciative inquiry trainning and 18 at control group (waiting-list). The design of this research is quasi experiment, with the untreated control group design with pretest-posttest. Every participant from the experiment and control group fill the self efficacy before and after they receive appreaciative inquiry response. The tools used in this research is appreciative inquiry training module, self-efficacy scale, observation sheet in the training, check the manipulation by focus group discussion and training evaluation sheets. The level of self-efficacy on salesperson is measured by using a scale of self-efficacy. Anova mixed results, with suggests that appreciative inquiry training can significantly improve self-efficacy on salesperson (p < 0.01, F = 218,087).